Hubungan Penyediaan Air Bersih dan Jamban Keluarga Dengan Kejadian Diare Pada Balita Di Desa Mala Kecamatan Manganitu Tahun 2015 - Dismo Katiandagho; Darwel Darwel (Poltekkes Kemenkes Padang, 2019)
Data from the Health Office of the Sangihe Regency up to June 2014, there were 708 diarrhea cases, the most cases were at age> 5 years totaling 430 cases; the highest cases were in the working area of ​​the Manganitu Health Center as many as 115 cases, and the village with the most diarrhea cases was Mala Village as many as 73 cases of diarrhea suffered by toddlers. The research objective is to determine the relationship between the provision of clean water and family latrines with the incidence of diarrhea in Mala Village, Manganitu District. This type of research is an observational analytic study with a cross sectional study design. The sample size in this study was the entire population of 73 toddlers being sampled. The results of bivariate data processing and analysis using the test chi square showed that there was a significant relationship between the provision of clean water facilities and the incidence of diarrhea in infants and there was a significant relationship between the provision of family latrines with the incidence of diarrhea in infants. The conclusion is that there is a significant relationship between the provision of clean water and the provision of family toilets with the occurrence of diarrhea in Mala Village, Manganitu District. Suggestions For people who do not have clean water facilities and family latrines to make or build clean water facilities and family latrines and the need for the role and support of health workers in the prevention of diarrheal diseases transmitted through the environment, officers always make observations and supervision to maintain the spread of disease based environment such as diarrhea.